Determination of Radius of Curvature for Teeth With Cycloid Profile; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Shatalov E. V. (Integrated Computer Control Systems in Mechanical Engineering, 2016)
Title screen